Method for preparing electrocatalyst by using waste lithium battery and application of electrocatalyst

The preparation of electrocatalysts through the acid leaching, sulfurization calcining and water immersion processes of the cathode powder of lithium battery is solved, and the problems of lithium battery recycling and PET plastic upgrade are achieved, efficient resource utilization and electrocatalytic performance are simplified, and the process flow is reduced and the cost is reduced. .

CN119194492APending Publication Date: 2024-12-27BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411221064.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium battery recycling technology has high cost and environmental impacts, and PET plastic recycling leads to performance degradation, and there is a lack of methods to effectively use waste lithium batteries to prepare electrocatalysts.

Method used

The cathode powder is obtained by disassemblying the fully discharged lithium battery, and the metal sulfide is prepared by acid leaching and thiourea calcining, and then water leaching is carried out to obtain an electrocatalyst, which is used in the field of electrochemical catalysis.

Benefits of technology

The resource utilization of lithium batteries has been realized, and the electrocatalysts prepared have high catalytic performance and low cost. They are suitable for the new method of converting PET plastics into glycolic acid, which simplifies the process flow and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194492A_ABST
    Figure CN119194492A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing an electrocatalyst by using a waste lithium battery and application of the electrocatalyst, and the method comprises the following steps: fully discharging the waste lithium battery, and disassembling to obtain cathode powder; adding a sulfuric acid solution into the cathode powder, and stirring to obtain a turbid liquid; carrying out suction filtration, washing and drying on the turbid liquid to obtain precursor powder; calcining the precursor powder and thiourea in a tubular furnace to obtain a metal sulfide; the mass ratio of the precursor powder to the thiourea is (1: 4)-(1: 6); and adding distilled water into the metal sulfide, stirring, carrying out suction filtration, washing and drying to obtain the electrocatalyst. The electrocatalyst LiMn0. 4Ni0. 4Co0. 2O2-H-ST with an excellent catalytic effect is prepared through simple acid leaching, sulfuration calcination and water leaching and is applied to the field of electrochemistry, PET plastic is converted into a high-value product glycollic acid, and resource utilization of waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a method for preparing an electrocatalyst using waste lithium batteries and its application. Background Art

[0002] With the rapid development of electric vehicles and portable electronic devices, the demand for lithium-ion batteries has increased dramatically. This has led to a sharp increase in the prices of major metals in lithium batteries, such as nickel (Ni), cobalt (Co), manganese (Mn), and lithium (Li). Therefore, it is very important to recycle the metal resources in lithium batteries. PET plastics are used on a large scale due to their advantages such as low cost, high stability, and high tensile strength. However, almost all PET plastics are discarded after completing the packaging task and discharged into the waste stream, leading to the "white pollution" problem. In order to protect the earth's ecological environment on which human beings depend for survival, the recycling of metals in waste lithium battery materials and the upgrading strategy of PET plastics have attracted considerable research attention.

[0003] At present, the commonly used methods for recovering Li, Ni, Co and Mn from the positive electrode materials of waste lithium batteries are pyrometallurgy and hydrometallurgy. In the pyrometallurgical process, the electrode materials are smelted and reduced at high temperature to reduce the Co, Ni and Mn oxides in the electrode materials to form metal alloys, and then further separated and purified to extract Co, Ni and Mn. However, this can easily lead to the loss of lithium and manganese in the battery during the process. In addition, the pyrometallurgical process has a huge environmental impact on energy consumption and gas emissions. In the hydrometallurgical process, waste lithium batteries are subjected to acid leaching and precipitation to extract Co, Ni and Mn from the electrode materials, and then further purified. However, the process is cumbersome, which increases the difficulty of recovering high-priced metals in waste lithium batteries. The recovery of Co, Ni and Mn by pyrometallurgy and hydrometallurgy inevitably results in high recovery costs and negative impacts on the environment. The main method for recycling PET waste is mechanical recycling, which includes classification, decontamination, drying, grinding and remelting to produce low-grade products. However, this recycling strategy is generally considered a "down-cycling" process, resulting in the degradation of the optical, thermal and mechanical properties of PET.

[0004] Therefore, how to provide a method for preparing electrocatalysts using waste lithium batteries, using cathode powder in waste lithium batteries as raw materials, and preparing composite metal electrocatalysts through acid leaching and sulfurization processes for use in the field of electrochemical catalysis is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] The purpose of the present invention is to provide a method and application of preparing an electrocatalyst using waste lithium batteries, so as to solve at least one of the above-mentioned technical problems.

[0006] To achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing an electrocatalyst using waste lithium batteries, the method comprising the following steps: S1, disassembling the waste lithium batteries after fully discharging them to obtain cathode powder; S2, adding sulfuric acid solution to the cathode powder and stirring to obtain a suspension; S3, filtering, washing and drying the suspension to obtain a precursor powder; S4, placing the precursor powder and thiourea in a tubular furnace for calcination to obtain a metal sulfide; the mass ratio of the precursor powder to the thiourea is 1:4 to 1:6; S5, adding distilled water to the metal sulfide, stirring, filtering, washing and drying to obtain an electrocatalyst.

[0007] In the first aspect, in S2, the concentration of the sulfuric acid solution is 2 to 4 mol / L.

[0008] In the first aspect, in S2, the stirring conditions include: a stirring temperature of 15 to 30°C, a stirring time of 1 to 3 days, and a stirring speed of 500 to 700 rpm.

[0009] In the first aspect, in S3, the filter cake after suction filtration is washed with water until it becomes neutral.

[0010] In the first aspect, placing the precursor powder and thiourea in a tubular furnace for calcination includes: placing the precursor powder downstream of a porcelain boat and placing the thiourea upstream of the porcelain boat; placing the porcelain boat in a tubular furnace for calcination.

[0011] In the first aspect, the calcination conditions include: heating from room temperature to 300°C to 500°C at a heating rate of 1 to 5°C / min in an argon atmosphere with a gas flow rate of 100 to 200 mL / min, keeping warm for 1 to 3 hours, and cooling to room temperature with the furnace temperature after calcination to obtain metal sulfide.

[0012] In the first aspect, in S5, the mass ratio of the metal sulfide to the distilled water is 1:20 to 1:25.

[0013] The second aspect of the present invention provides an application of preparing an electrocatalyst using waste lithium batteries, wherein the steps of preparing an electrocatalyst using the method for preparing an electrocatalyst using waste lithium batteries described in the first aspect to convert PET plastic into glycolic acid include: (1) dissolving PET plastic in an alkaline solution, performing solid-liquid separation after a hydrolysis reaction, and obtaining an ethylene glycol solution; (2) preparing a mixed solution of 192 μL of anhydrous ethanol and 8 μL of a naphthol film solution, adding 2 mg of the electrocatalyst to the mixed solution, and performing ultrasonic dispersion to obtain a uniform solution; dropping the uniform solution on nickel foam, and drying at room temperature to obtain a Electrocatalyst / nickel foam; (3) assembling an H-type electrolytic cell, using the electrocatalyst / nickel foam as the working electrode, Hg / HgO as the reference electrode, and a platinum sheet as the counter electrode, an anion exchange membrane separating the cathode chamber and the anode chamber, the working electrode and the reference electrode are both located in the anode chamber, and the counter electrode is located in the cathode chamber; the electrolytes in the anode chamber and the cathode chamber are both a mixed solution of 55 mL of a 1 mol / L KOH solution and a 0.3 mol / L ethylene glycol solution; (4) after the assembly is completed, applying voltage to the H-type electrolytic cell to perform electrocatalytic oxidation to obtain glycolic acid.

[0014] In the second aspect, in step (1), the alkaline solution is a 1.5 mol / L KOH solution; the conditions of the hydrothermal reaction include: a reaction temperature of 180° C. and a reaction time of 2 h.

[0015] In the second aspect, in step (4), the conditions for the electrocatalytic oxidation include: reacting at room temperature and normal pressure, and a voltage of 0.73 to 0.93 V vs. RHE.

[0016] Beneficial effects:

[0017] The present invention provides a method for preparing an electrocatalyst using waste lithium batteries. First, the waste lithium batteries after full discharge are disassembled to obtain cathode powder, so as to realize resource utilization of waste; secondly, the cathode powder is acid-leached with a sulfuric acid solution to extract metal ions to obtain a suspension, and the suspension is filtered, washed, and dried to obtain a precursor powder to remove excess sulfuric acid and make the precursor powder neutral; then, the precursor powder is sulfurized and calcined with thiourea to obtain a metal sulfide; finally, distilled water is added to the metal sulfide for water leaching, and the electrocatalyst is obtained by filtering, washing, and drying to remove unbound ions. The composite metal electrocatalyst prepared by the present invention using the cathode powder in the waste lithium battery as a raw material through acid leaching, sulfurization, water leaching and other processes can be widely used in the field of electrochemistry, and the preparation method is simple and the process is short, so as to realize resource utilization of waste.

[0018] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of this specification or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 A flow chart of a method for preparing an electrocatalyst using waste lithium batteries provided by the present invention;

[0021] Figure 2 It is a comparison diagram of LSV curves of electrocatalysts prepared in the examples of the present invention and the comparative examples;

[0022] Figure 3 It is a comparison diagram of FE curves of the electrocatalyst prepared in Example 1 of the present invention and the comparative example;

[0023] Figure 4 This is a SEM image of the electrocatalyst prepared in Example 1 of the present invention;

[0024] Figure 5 This is a SEM image of the electrocatalyst prepared in Comparative Example 1 of the present invention;

[0025] Figure 6 This is the SEM image of the electrocatalyst prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0026] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0027] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained by existing methods.

[0029] See also Figure 1 The present application provides a method for preparing an electrocatalyst using waste lithium batteries, the method comprising the following steps: S1, disassembling the waste lithium batteries after fully discharging them to obtain cathode powder; S2, adding sulfuric acid solution to the cathode powder and stirring to obtain a suspension; S3, filtering, washing, and drying the suspension to obtain a precursor powder; S4, placing the precursor powder and thiourea in a tubular furnace for calcination to obtain a metal sulfide; the mass ratio of the precursor powder to the thiourea is 1:4 to 1:6; S5, adding distilled water to the metal sulfide, stirring, filtering, washing, and drying to obtain an electrocatalyst.

[0030] Specifically, the present invention provides a method for preparing an electrocatalyst using waste lithium batteries. First, the waste lithium batteries after full discharge are disassembled to obtain cathode powder, so as to realize the resource utilization of waste; secondly, the cathode powder is acid-leached with sulfuric acid solution to extract metal ions to obtain a suspension, and the suspension is filtered, washed, and dried to obtain a precursor powder to remove excess sulfuric acid and make the precursor powder neutral; then, the precursor powder is sulfurized and calcined with thiourea to obtain a metal sulfide; finally, distilled water is added to the metal sulfide for water immersion, and the electrocatalyst is obtained by filtering, washing, and drying to remove unbound ions. The composite metal electrocatalyst prepared by the present invention using the cathode powder in the waste lithium battery as a raw material through acid leaching, sulfurization, water leaching and other processes can be widely used in the field of electrochemistry, and the preparation method is simple and the process is short, so as to realize the resource utilization of waste.

[0031] In some possible embodiments, in S2, the concentration of the sulfuric acid solution is 2-4 mol / L.

[0032] In some possible embodiments, in S2, the stirring conditions include: a stirring temperature of 15 to 30°C, a stirring time of 1 to 3 days, and a stirring speed of 500 to 700 rpm.

[0033] Those skilled in the art can understand that the purchased concentrated sulfuric acid is diluted by measuring 5-10 mL of concentrated sulfuric acid and adding it to 30-60 mL of water for dilution to prepare a 2-4 mol / L sulfuric acid solution for acid leaching of the cathode powder, and at the same time adjusting the temperature, time and rate during the acid leaching process to increase the leaching rate of metal ions in the cathode powder.

[0034] In some possible embodiments, in S3, the filter cake after suction filtration is washed with water until it becomes neutral.

[0035] This is because sulfuric acid solution or acidic ions still exist in the filter cake after filtration. By washing with water, the sulfuric acid solution can be further diluted or the acidic ions can be removed to avoid affecting the subsequent sulfidation calcination.

[0036] In some possible embodiments, placing the precursor powder and thiourea in a tubular furnace for calcining includes: placing the precursor powder downstream of a porcelain boat and placing the thiourea upstream of the porcelain boat; placing the porcelain boat in a tubular furnace for calcining.

[0037] In some possible embodiments, the calcination conditions include: heating from room temperature to 300°C to 500°C at a heating rate of 1 to 5°C / min in an argon atmosphere with a gas flow rate of 100 to 200 mL / min, keeping warm for 1 to 3 hours, and cooling to room temperature with the furnace temperature after the calcination to obtain metal sulfide.

[0038] Those skilled in the art will appreciate that the calcination temperature is 300-500° C., thiourea decomposes and reacts with the precursor powder to generate composite metal sulfides.

[0039] In some possible embodiments, in S5, the mass ratio of the metal sulfide to the distilled water is 1:20 to 1:25.

[0040] This is because, by controlling the mass ratio of metal sulfide to distilled water to 1:20 to 1:25, unbound metal ions can be further removed, so that the prepared electrocatalyst has a lower overvoltage and a larger current density, thereby improving the catalytic performance of the electrocatalyst.

[0041] Based on a general inventive concept, the present application also provides an application of preparing an electrocatalyst using waste lithium batteries, and the steps of preparing an electrocatalyst using the method for preparing an electrocatalyst using waste lithium batteries described in the first aspect to convert PET plastic into glycolic acid include:

[0042] (1) dissolving PET plastic in an alkaline solution, performing solid-liquid separation after hydrolysis reaction, and obtaining an ethylene glycol solution;

[0043] (2) preparing a mixed solution of 192 μL of anhydrous ethanol and 8 μL of naphthol film solution, adding 2 mg of the electrocatalyst to the mixed solution, and performing ultrasonic dispersion to obtain a uniform solution; dropping the uniform solution on nickel foam, and drying at room temperature to obtain an electrocatalyst / nickel foam;

[0044] (3) Assembling an H-type electrolytic cell, using the electrocatalyst / nickel foam as the working electrode, Hg / HgO as the reference electrode, and a platinum sheet as the counter electrode, an anion exchange membrane separating the cathode chamber and the anode chamber, the working electrode and the reference electrode are both located in the anode chamber, and the counter electrode is located in the cathode chamber; the electrolyte in the anode chamber and the cathode chamber is a mixed solution of 55 mL of a 1 mol / L KOH solution and a 0.3 mol / L ethylene glycol solution;

[0045] (4) After the assembly is completed, a voltage is applied to the H-type electrolytic cell to perform electrocatalytic oxidation to obtain glycolic acid.

[0046] Specifically, the waste PET plastic is degraded, and the terephthalic acid solid is precipitated from the reaction solution through hydrothermal reaction and pH adjustment. After solid-liquid separation, an ethylene glycol solution is obtained. After the concentration of the ethylene glycol solution is calibrated, it can be directly used as a raw material for an electrocatalytic reaction, and an electrocatalyst is used as a catalyst for the electrocatalytic reaction to prepare glycolic acid. The present invention provides a new method for preparing glycolic acid using PET plastic, which is simple, easy to operate, and highly efficient.

[0047] In conjunction with the second aspect of the present application, in step (1), the alkaline solution is a 1.5 mol / L KOH solution; the conditions of the hydrothermal reaction include: a reaction temperature of 180° C. and a reaction time of 2 h.

[0048] In conjunction with the second aspect of the present application, in step (4), the conditions for the electrocatalytic oxidation include: reacting at room temperature and normal pressure, and a voltage of 0.73 to 0.93 V vs. RHE.

[0049] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0050] Example 1

[0051] The method for preparing an electrocatalyst using waste lithium batteries specifically comprises the following steps:

[0052] (1) After fully discharging the discarded lithium batteries in the laboratory, they were disassembled to obtain cathode powder; wherein the proportion of lithium in the cathode powder was 26532.12 mg / kg;

[0053] (2) Weigh 2 g of cathode powder and add 70 mL of 2.63 mol / L sulfuric acid solution, stir for 2 days at a temperature of 25° C. and a stirring speed of 600 rpm to obtain a suspension;

[0054] (3) The suspension is filtered to obtain a filtrate and a filter cake, wherein the filtrate is the first Li leaching solution, and the Li concentration in the filtrate is measured to be 1019.7 mg / L; the filter cake is washed with water until it is neutral, and then dried to obtain a precursor powder;

[0055] (4) placing the precursor powder downstream of the porcelain boat and placing thiourea upstream of the porcelain boat; placing the porcelain boat in a tube furnace for calcination, and cooling the furnace temperature to room temperature after calcination to obtain metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 400 , wherein the mass ratio of the precursor powder to thiourea is 1:4; the calcination conditions include: heating from room temperature to 400°C at a heating rate of 2°C / min under an argon atmosphere with a gas flow rate of 150 mL / min, and keeping the temperature for 2 hours;

[0056] (5) Weigh 2g of metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 400 40 mL of distilled water was added, stirred, filtered, washed and dried to obtain the electrocatalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 400 The Li concentration of the filtrate after filtration was measured to be 288.07 mg / L, from which it can be inferred that the Li leaching rate is as high as 93.15%.

[0057] The electrocatalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 400 For electrocatalysis, the steps to convert PET plastic into glycolic acid include:

[0058] (1) 1.8 g of PET plastic was added to 30 mL of 1.5 mol / L KOH solution, and a hydrolysis reaction was carried out at 180° C. After 2 h, a reaction solution was obtained, and concentrated sulfuric acid was added for acidification. Terephthalic acid solid was precipitated from the reaction solution, and solid-liquid separation was performed to obtain an ethylene glycol solution, and the concentration of ethylene glycol was calibrated using a chromatograph;

[0059] (2) Prepare a mixed solution of 192 μL of anhydrous ethanol and 8 μL of naphthol film solution, and add 2 mg of electrocatalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 400, ultrasonically disperse for 30 minutes to obtain a uniform solution; drop 20 μL of the uniform solution on the front and back sides of a 1 cm×1.5 cm nickel foam five times each, and dry at room temperature to obtain an electrocatalyst / nickel foam;

[0060] (3) Assembling an H-type electrolytic cell, using electrocatalyst / nickel foam as the working electrode, Hg / HgO as the reference electrode, and platinum sheet as the counter electrode, the cathode chamber and the anode chamber are separated by an anion exchange membrane, the working electrode and the reference electrode are both located in the anode chamber, and the counter electrode is located in the cathode chamber; the electrolyte in the anode chamber and the cathode chamber is a mixed solution of 55 mL of 1 mol / L KOH solution and 0.3 mol / L ethylene glycol solution;

[0061] (4) After the assembly is completed, a voltage is applied to the H-type electrolytic cell to perform electrocatalytic oxidation to obtain glycolic acid, and the product is detected.

[0062] Example 2

[0063] The method for preparing an electrocatalyst using waste lithium batteries specifically comprises the following steps:

[0064] (1) After fully discharging discarded lithium batteries in the laboratory, disassembling them to obtain cathode powder;

[0065] (2) Weigh 2 g of cathode powder and add 70 mL of 2.63 mol / L sulfuric acid solution, stir for 2 days at a temperature of 25° C. and a stirring speed of 600 rpm to obtain a suspension;

[0066] (3) filtering the suspension to obtain a filtrate and a filter cake; washing the filter cake with water until it is neutral, and drying it to obtain a precursor powder;

[0067] (4) placing the precursor powder downstream of the porcelain boat and placing thiourea upstream of the porcelain boat; placing the porcelain boat in a tube furnace for calcination, and cooling the furnace temperature to room temperature after calcination to obtain metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 300 , wherein the mass ratio of the precursor powder to thiourea is 1:4; the calcination conditions include: heating from room temperature to 300°C at a heating rate of 2°C / min under an argon atmosphere with a gas flow rate of 150 mL / min, and keeping the temperature for 2 hours;

[0068] (5) Weigh 2g of metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 300 40 mL of distilled water was added, stirred, filtered, washed and dried to obtain the electrocatalyst LiMn 0.4 Ni0.4 Co 0.2 O2-HS 300 .

[0069] The electrocatalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 300 Used in the field of electrocatalysis, PET plastic is converted into glycolic acid, and the steps of electrocatalytic oxidation are the same as those in Example 1.

[0070] Example 3

[0071] The method for preparing an electrocatalyst using waste lithium batteries specifically comprises the following steps:

[0072] (1) After fully discharging discarded lithium batteries in the laboratory, disassembling them to obtain cathode powder;

[0073] (2) Weigh 2 g of cathode powder and add 70 mL of 2.63 mol / L sulfuric acid solution, stir for 2 days at a temperature of 25° C. and a stirring speed of 600 rpm to obtain a suspension;

[0074] (3) filtering the suspension to obtain a filtrate and a filter cake; washing the filter cake with water until it is neutral, and drying it to obtain a precursor powder;

[0075] (4) placing the precursor powder downstream of the porcelain boat and placing thiourea upstream of the porcelain boat; placing the porcelain boat in a tube furnace for calcination, and cooling the furnace temperature to room temperature after calcination to obtain metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 350 , wherein the mass ratio of the precursor powder to thiourea is 1:4; the calcination conditions include: heating from room temperature to 350°C at a heating rate of 2°C / min under an argon atmosphere with a gas flow rate of 150 mL / min, and keeping the temperature for 2 hours;

[0076] (5) Weigh 2g of metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 350 40 mL of distilled water was added, stirred, filtered, washed and dried to obtain the electrocatalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 350 .

[0077] The electrocatalyst LiMn 0.4 Ni 0.4 Co0.2 O2-HS 350 Used in the field of electrocatalysis, PET plastic is converted into glycolic acid, and the steps of electrocatalytic oxidation are the same as those in Example 1.

[0078] Example 4

[0079] The method for preparing an electrocatalyst using waste lithium batteries specifically comprises the following steps:

[0080] (1) After fully discharging discarded lithium batteries in the laboratory, disassembling them to obtain cathode powder;

[0081] (2) Weigh 2 g of cathode powder and add 70 mL of 2.63 mol / L sulfuric acid solution, stir for 2 days at a temperature of 25° C. and a stirring speed of 600 rpm to obtain a suspension;

[0082] (3) filtering the suspension to obtain a filtrate and a filter cake; washing the filter cake with water until it is neutral, and drying it to obtain a precursor powder;

[0083] (4) placing the precursor powder downstream of the porcelain boat and placing thiourea upstream of the porcelain boat; placing the porcelain boat in a tube furnace for calcination, and cooling the furnace temperature to room temperature after calcination to obtain metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 450 , wherein the mass ratio of the precursor powder to thiourea is 1:4; the calcination conditions include: heating from room temperature to 450°C at a heating rate of 2°C / min under an argon atmosphere with a gas flow rate of 150 mL / min, and keeping the temperature for 2 hours;

[0084] (5) Weigh 2g of metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 450 40 mL of distilled water was added, stirred, filtered, washed and dried to obtain the electrocatalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 450 .

[0085] The electrocatalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 450 Used in the field of electrocatalysis, PET plastic is converted into glycolic acid, and the steps of electrocatalytic oxidation are the same as those in Example 1.

[0086] Comparative Example 1

[0087] Compared with Example 1, the sulfurization process is not performed, and the method for preparing an electrocatalyst using waste lithium batteries specifically includes the following steps:

[0088] (1) After fully discharging discarded lithium batteries in the laboratory, disassembling them to obtain cathode powder;

[0089] (2) Weigh 2 g of cathode powder and add 70 mL of 2.63 mol / L sulfuric acid solution, stir for 2 days at a temperature of 25° C. and a stirring speed of 600 rpm to obtain a suspension;

[0090] (3) The suspension is filtered to obtain a filtrate and a filter cake, the filtrate being the first Li leaching solution, and the Li concentration in the filtrate is measured; the filter cake is washed with water until it is neutral, and dried to obtain the precursor powder LiMn 0.4 Ni 0.4 Co 0.2 O2.

[0091] The precursor powder LiMn 0.4 Ni 0.4 Co 0.2 O2 is used as an electrocatalyst in the field of electrocatalysis to convert PET plastic into glycolic acid, and the steps of electrocatalytic oxidation are the same as those in Example 1.

[0092] Comparative Example 2

[0093] Compared with Example 1, no water washing is performed after sulfurization. The method for preparing an electrocatalyst using waste lithium batteries specifically includes the following steps:

[0094] (1) After fully discharging discarded lithium batteries in the laboratory, disassembling them to obtain cathode powder;

[0095] (2) Weigh 2 g of cathode powder and add 70 mL of 2.63 mol / L sulfuric acid solution, stir for 2 days at a temperature of 25° C. and a stirring speed of 600 rpm to obtain a suspension;

[0096] (3) The suspension is filtered to obtain a filtrate and a filter cake, wherein the filtrate is the first Li leaching solution, and the Li concentration in the filtrate is measured; the filter cake is washed with water until it is neutral, and the precursor powder is obtained after drying;

[0097] (4) placing the precursor powder downstream of the porcelain boat and placing thiourea upstream of the porcelain boat; placing the porcelain boat in a tube furnace for calcination, and cooling the furnace temperature to room temperature after calcination to obtain metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 400, wherein the mass ratio of the precursor powder to thiourea is 1:4; the calcination conditions include: heating from room temperature to 400°C at a heating rate of 2°C / min in an argon atmosphere with a gas flow rate of 150 mL / min, and keeping the temperature for 2 hours.

[0098] The metal sulfide LiMn 0.4 Ni 0.4 Co 0.2 O2-S 400 The electrocatalyst is used in the field of electrocatalysis to convert PET plastic into glycolic acid, and the electrocatalytic oxidation steps are the same as those in Example 1.

[0099] The electrocatalysts prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests. The LSV performance test results are shown in FIG. Figure 2 As shown, the Faraday efficiency test results are as follows Figure 3 As shown. Figure 2 It can be seen that LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 400 With LiMn 0.4 Ni 0.4 Co 0.2 O2-S 400 and LiMn 0.4 Ni 0.4 Co 0.2 Compared with O2, the catalyst after sulfidation and secondary lithium precipitation has lower overvoltage and greater current density. The performance of the unsulfided catalyst is very poor. After sulfidation, a sulfide heterostructure is formed to promote electron transfer, making the catalyst have excellent activity. Under the same preparation conditions, catalysts with different calcination temperatures of 300, 350, 400 and 450℃ were prepared. The LSV performance Figure 2 It can be seen that when the calcination temperature is 400℃, the best activity is shown. When the sulfurization temperature is around 400℃, NiCo2S4, MnS and Ni x S y Multiphase active materials such as Li-ion batteries are rich in Ni, Co, and Mn. Therefore, when the sulfurization calcination temperature is 400°C, it is easy to form LiMn with synergistic effects of multiphase active materials. 0.4 Ni 0.4 Co 0.2 O2-HS 400 , which has excellent catalytic activity for ethylene glycol oxidation. On the other hand, for the optimal catalyst LiMn 0.4 Ni 0.4 Co 0.2 O2-HS 400, was tested in pure KOH electrolyte, and its overpotential was much larger than that of the mixed electrolyte of KOH and ethylene glycol, which indicates that its activity comes from the oxidation of ethylene glycol.

[0100] from Figure 3 As can be seen from the figure, the test potential is distributed in the range of 0.63V vs.RHE to 1.03V vs.RHE. As the voltage increases, the Faraday efficiency of glycolic acid increases. 0.4 Ni 0.4 Co 0.2 O2-HS 400 With LiMn 0.4 Ni 0.4 Co 0.2 O2-S 400 The maximum Faradaic efficiencies of the products at 0.83 V vs. RHE are 91.37% and 75.32%, respectively. 0.4 Ni 0.4 Co 0.2 O2, the Faraday efficiency reaches a maximum value of 53.24% at 0.93V vs. RHE. As the voltage continues to increase, the Faraday efficiency of glycolic acid gradually decreases. The experimental results show that at the same potential, the LiMn prepared by the present invention 0.4 Ni 0.4 Co 0.2 O2-HS 400 The catalytic activity is better than that of LiMn 0.4 Ni 0.4 Co 0.2 O2-S 400 and LiMn 0.4 Ni 0.4 Co 0.2 O2, at a wide potential of 0.73V vs.RHE ~ 0.93V vs.RHE, the Faradaic efficiency of glycolic acid can reach more than 85%, with excellent electrocatalytic PET-derived ethylene glycol oxidation activity and selectivity.

[0101] From SEM Figure 4-6 It can be seen that the catalyst after sulfidation, calcination and water immersion has a denser structure and thus has better catalytic activity.

[0102] In summary, the technical solution provided by the present invention has the following advantages:

[0103] (1) The present invention uses waste lithium battery cathode powder as raw material, and uses acid leaching, sulfurization calcination and water leaching to achieve Li leaching of up to 93.15%. At the same time, the catalyst LiMn is obtained by controlling the temperature. 0.4 Ni 0.4 Co 0.2 O2-HST By effectively regulating the catalyst preparation conditions, waste lithium battery materials are successfully recycled and reused, and become an efficient electrocatalyst for upgrading waste PET to C2 products. The present invention also has the advantages of easy control of the preparation method, good treatment effect, large treatment capacity, low energy consumption, low raw material cost, and easy to obtain the target product.

[0104] (2) The present invention uses metal sulfides recovered from waste lithium battery materials as electrocatalysts for converting PET derivatives into glycolic acid. The catalyst is used as a cathode electrode and added to a reaction cell. It has good catalytic activity and selectivity for the oxidation of PET derivatives. In the potential range of 0.73V vs.RHE to 0.93V vs.RHE, the Faraday efficiency of glycolic acid is above 85%. At a voltage of 0.83V vs.RHE, the test current is stable, and the Faraday efficiency of glycolic acid is as high as 91.37%. It has good application prospects in the field of electrochemistry.

[0105] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0106] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0107] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an electrocatalyst using waste lithium batteries, characterized in that: The method comprises the following steps: S1. After fully discharging the discarded lithium battery, dismantle it to obtain cathode powder; S2, adding sulfuric acid solution to the cathode powder and stirring to obtain a suspension; S3, filtering, washing and drying the suspension to obtain a precursor powder; S4, placing the precursor powder and thiourea into a tubular furnace for calcination to obtain metal sulfide; the mass ratio of the precursor powder to the thiourea is 1:4 to 1:6; S5. Add distilled water to the metal sulfide, stir, filter, wash and dry to obtain an electrocatalyst.

2. The method for preparing an electrocatalyst using waste lithium batteries according to claim 1, characterized in that: In the S2, the concentration of the sulfuric acid solution is 2-4 mol / L.

3. The method for preparing an electrocatalyst using waste lithium batteries according to claim 2, characterized in that: In S2, the stirring conditions include: a stirring temperature of 15 to 30°C, a stirring time of 1 to 3 days, and a stirring speed of 500 to 700 rpm.

4. The method for preparing an electrocatalyst using waste lithium batteries according to claim 1, characterized in that: In S3, the filter cake after suction filtration is washed with water until it becomes neutral.

5. The method for preparing an electrocatalyst using waste lithium batteries according to claim 1, characterized in that: The step of placing the precursor powder and thiourea in a tubular furnace for calcining comprises: placing the precursor powder downstream of a porcelain boat and placing the thiourea upstream of the porcelain boat; and placing the porcelain boat in a tubular furnace for calcining.

6. The method for preparing an electrocatalyst using waste lithium batteries according to claim 5, characterized in that: The calcination conditions include: heating from room temperature to 300°C to 500°C at a heating rate of 1 to 5°C / min in an argon atmosphere with a gas flow rate of 100 to 200 mL / min, keeping the temperature for 1 to 3 hours, and cooling to room temperature with the furnace temperature after the calcination to obtain metal sulfide.

7. The method for preparing an electrocatalyst using waste lithium batteries according to claim 1, characterized in that: In the S5, the mass ratio of the metal sulfide to the distilled water is 1:20 to 1:

25.

8. An application of preparing electrocatalyst using waste lithium batteries, characterized in that: The steps of converting PET plastic into glycolic acid by using the method for preparing an electrocatalyst using waste lithium batteries as described in any one of claims 1 to 7 include: (1) dissolving PET plastic in an alkaline solution, performing solid-liquid separation after hydrolysis reaction, and obtaining an ethylene glycol solution; (2) preparing a mixed solution of 192 μL of anhydrous ethanol and 8 μL of naphthol film solution, adding 2 mg of the electrocatalyst to the mixed solution, and performing ultrasonic dispersion to obtain a uniform solution; dropping the uniform solution on nickel foam, and drying at room temperature to obtain an electrocatalyst / nickel foam; (3) Assembling an H-type electrolytic cell, using the electrocatalyst / nickel foam as the working electrode, Hg / HgO as the reference electrode, and a platinum sheet as the counter electrode, an anion exchange membrane separating the cathode chamber and the anode chamber, the working electrode and the reference electrode are both located in the anode chamber, and the counter electrode is located in the cathode chamber; the electrolyte in the anode chamber and the cathode chamber is a mixed solution of 55 mL of a 1 mol / L KOH solution and a 0.3 mol / L ethylene glycol solution; (4) After the assembly is completed, a voltage is applied to the H-type electrolytic cell to perform electrocatalytic oxidation to obtain glycolic acid.

9. The use of waste lithium batteries to prepare electrocatalysts according to claim 7, characterized in that: In step (1), the alkaline solution is a 1.5 mol / L KOH solution; The conditions of the hydrothermal reaction include: reaction temperature of 180° C. and reaction time of 2 h.

10. The use of waste lithium batteries to prepare electrocatalysts according to claim 7, characterized in that: In step (4), the conditions for the electrocatalytic oxidation include: reacting at room temperature and normal pressure, and a voltage of 0.73 to 0.93 V vs. RHE.